Diversification times among Brassica (Brassicaceae) crops suggest hybrid formation after 20 million years of divergence1. Issue 1 (1st January 2014) - Arias, Tatiana; Beilstein, Mark A.; Tang, Michelle; McKain, Michael R.; Pires, J. Chris
Abstract : Premise of the study: Cruciferous vegetables, many of which are in the genus Brassica (Brassicaceae), are prized for their nutritive value and have been cultivated for thousands of years. There are numerous wild northwestern Mediterranean species in the tribe Brassiceae, and it is therefore assumed this center of diversity is also the region of origin. Within the tribe, the Nigra and Oleracea clades contain the three diploid Brassica crops, B. oleracea, B. rapa, and B. nigra . These three species hybridized in the past to form the tetraploid crop species B. juncea, B. carinata, and B. napus . Collectively, these crop Brassicas have been thought to be closely related because they can still hybridize. Methods: Using a combination of molecular phylogenetics, diversification analysis, and historical biogeography, we evaluated the relationships and origins of four nested clades: the tribe Brassiceae, the Nigra‐Oleracea clade, the core Oleracea (includes B. oleracea + B. rapa and their respective wild relatives), and Brassica oleracea and relatives. Key results: We found evidence that the tribe originated around the intersection forming between the Arabian Peninsula and Saharan Africa approximately 24 million years ago (Mya). Our data also suggest that the maternal genomes of the three diploid crop Brassicas are not closely related and that the Nigra‐Oleracea clade diverged 20 Mya. Finally, our analyses indicate that the core Oleracea lineage giving rise to B. oleracea + B. rapa originated ≈3 Mya in the northeastern Mediterranean, from where ancestors of B. oleracea spread through Europe and B. rapa to Asia. Conclusions: These results challenge previous hypotheses about the biogeographic origins of the tribe Brassiceae and the crop Brassica species and appear to be correlated with major geological and climatic events in the Mediterranean basin.